1994
DOI: 10.1093/cvr/28.9.1301
|View full text |Cite
|
Sign up to set email alerts
|

Postreperfusion inflammation: a model for reaction to injury in cardiovascular disease

Abstract: In the preceding section various strategies to interdict postreperfusion inflammatory injury of the myocardium were proposed; effectively the strategies were aimed at specific targets such as stimuli which control cell motility, mechanisms of alteration of cell phenotype, and the induction of cell adhesion and proliferation. It is of interest to see how similar these targets would be if one were to attempt a cell biological approach to vascular injury which results in subintimal hyperplasia. In the latter, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
100
0
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(104 citation statements)
references
References 0 publications
1
100
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8] One cellular response that might favor tissue repair is early resorption of denatured matrix proteins. Neutrophil-derived MMP-9 is stored in tertiary granules and released on chemotactic stimulation.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] One cellular response that might favor tissue repair is early resorption of denatured matrix proteins. Neutrophil-derived MMP-9 is stored in tertiary granules and released on chemotactic stimulation.…”
mentioning
confidence: 99%
“…Inflammation plays an important role in the healing of tissue after injury. [1][2][3][4][5][6][7][8][9] However, there is evidence that the accelerated inflammatory response may also extend tissue injury. Clinical and experimental studies showed that the inflammatory response to myocardial infarction is associated with the induction of cytokines such as tumor necrosis factor (TNF)-␣, interleukin (IL)-1␤, and IL-6, which are thought to act in a "cascade fashion."…”
mentioning
confidence: 99%
“…1 Extensive investigations into the pathophysiology of many clinically relevant major tissue injuries, e.g., myocardial infarction, stroke, organ transplantation, revealed that the inevitable early recruitment of neutrophils into the tissue may not only remove necrotic cells, but also may cause damage to healthy cells. 2,3 Thus, neutrophils can considerably aggravate the initial injury and contribute to long-term morbidity and mortality. Because of the potential detrimental effects of neutrophils in many clinical situations, various aspects of the basic mechanisms of neutrophil accumulation at an inflammatory site and the molecular mechanisms of injury have been subject to extensive investigation during the last decade.…”
mentioning
confidence: 99%